The Birth of the Infinite Cluster: Finite-size Scaling in Percolation - Borgs, Christian; Chayes, Jennifer; Kesten, H.; Spencer, J. (Communications in Mathematical Physics 224, 2000)
We address the question of nite-size scaling in percolation by studying bond percolation in a nite box of side length n, both in two and in higher dimensions. In dimension d = 2, we obtain a complete characterization of nite-size scaling. In dimensions d > 2, we establish the same results under a set of hypotheses related to so-called scaling and hyperscaling postulates which are widely believed to hold up to d = 6. As a function of the size of the box, we determine the scaling window in which the system behaves critically. We characterize criticality in terms of the scaling of the sizes of the largest clusters in the box: incipient in nite clusters which give rise to the in nite cluster. Within the scaling window, we show that the size of the largest cluster behaves like ndn, where n is the probability at criticality that the origin is connected to the boundary of a box of radius n. We also show that, inside the window, there are typically many clusters of scale ndn, and hence that he" incipient in nite cluster is not unique. Below the window, we show that the size of the largest cluster scales like d log(n=), where is the correlation length, and again, there are many clusters of this scale. Above the window, we show that the size of the largest cluster scales like ndP1, where P1 is the in nite cluster density, and that there is only one cluster of this scale. Our results are nite-dimensional analogues of results on the dominant component of the Erd]os-Renyi mean-fi eld random graph model.